Reasons for Low Passenger Flow of City Railway Renovated from Existing Lines and Countermeasures - XU Xingfang; WANG Haoyue; HUANG Jie; HONG Shiqi (Chengshi guidao jiaotong yanjiu)
［Objective］ Recently, the passenger flow in the city railway renovated from existing lines is generally low, it is necessary to systematically analyze the reasons and put forward corresponding countermeasures to improve the operational efficiency and facilitate the travel of suburban passengers. ［Method］ Based on researches of 3 city railways renovated from existing lines in Yangtze River Delta region, especially the multi-dimensional analysis of the annual passenger flow in Shanghai Jinshan Railway, the characteristics of passenger flow distribution are summarized from time and space two dimensions. The composition of the city railway passenger flow and the characteristics of its temporal and spatial fluctuations are summarized based on the quantitative analysis. The passenger flow demand and the impact of the city railway on the residents along the line are qualitatively analyzed according to the long-term observation of the railway staff. Combining the results of the quantitative and qualitative analyses and focusing on the specific passenger flow status of the 3 city railways, factors affecting the city railway passenger flow volume are analyzed in detail, corresponding measures to increase the passenger flow volume are put forward. ［Result & Conclusion］ The reasons for the city railway low passenger flow in China mainly include factors related to the characteristics of city passenger flow itself, limitations of line condition, limitations of train operation plan, insufficient travel convenience, and weak market competitiveness. The countermeasures include improving the planning and construction of the line network, enhancing the line passing capacity, optimizing train operation plans, improving the connection and transfer between lines, adhering to the public welfare fare policy, promoting the comprehensive transformation guided by public transportation and etc.